1975
DOI: 10.1111/j.1471-0528.1975.tb00719.x
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Thyroid “Test Profile” in Habitual Abortion

Abstract: Summary A characteristic thyroid test profile is observed in pregnancy; it consists of an elevated serum thyroxine (TJ), thyroxine binding globulin (TBG) and electro‐phoretic index (EI) with lowered triiodothyronine resin uptake (T3U), the free thyroxine index (FTI) remaining in the normal range. An investigation was made of progressive changes in these parameters in 70 normal pregnant women, 34 pregnant women with a past history of habitual abortion who carried to term, seven habitual aborters who miscarried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

1980
1980
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…The highly significant increased plasma cAMP levels after interruption of Novothyral therapy support the contention that increased activ ity of the thyroid gland might contribute to the increased plasma cAMP levels that were seen in normal pregnancy. On the other hand, during the third trimester, T3 is more elevated and most likely its unbound fraction too, compen sating an inadequate increase of thyroxin at maximum amounts of TBG, in order to keep the euthyroid state (Kaiman et al, 1973;Rastogi et al, 1974;Winikoff and Malinek, 1975). These elevated T3 concentrations might elevate cAMP levels in tissues and plasma by way of increased adenylcyclase activity by (3-receptor stimulation (Karlberg et al, 1974).…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly significant increased plasma cAMP levels after interruption of Novothyral therapy support the contention that increased activ ity of the thyroid gland might contribute to the increased plasma cAMP levels that were seen in normal pregnancy. On the other hand, during the third trimester, T3 is more elevated and most likely its unbound fraction too, compen sating an inadequate increase of thyroxin at maximum amounts of TBG, in order to keep the euthyroid state (Kaiman et al, 1973;Rastogi et al, 1974;Winikoff and Malinek, 1975). These elevated T3 concentrations might elevate cAMP levels in tissues and plasma by way of increased adenylcyclase activity by (3-receptor stimulation (Karlberg et al, 1974).…”
Section: Commentmentioning
confidence: 99%
“…Another source of cAMP in maternal plasma, especially concerning the second cAMP plasma peak, might be the thyroid gland as follows from our observations of thyroid state and cAMP alterations during Novothyral substitution and after interruption of therapy. Thyroxine-binding globulin (TBG) is maximally increased at the time of the second cAMP peak, and thyroid function is supposed to be increased to keep the turnover of T4 normal at that high TBG levels (Kantian et al, 1973;Rastogi et al, 1974;Winikoff and Malinek, 1975). The thyroid gland is often enlarged in pregnancy.…”
Section: Commentmentioning
confidence: 99%
“…Since pregnancy is generally associated with hyperthyroxinemia, the degree of hypothyroxinemia might reflect the severity of toxemia [2], The pregnant patients who gave birth to abnormal infants showed an important decrease in the level of thyroxine-binding globulin (TBG) at 15-16 weeks gestation [3] and also the relation between a low TBG level and habitual abortion was reported [4], We encountered only a few studies on the relationship be tween thyroid hormones and birth weights in toxemia. One of these studies showed a significant correlation between lower birth weight and TBG as well as triiodothy ronine uptake (TiU) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in thyroxine-binding globulin (TBG) in particular merits further examination. A relationship between a low TBG level and habitual abortion has been reported [3,4], In a recent study [5], significantly lower values of TBG were found in women with spontaneous abortion. Thus, the measurement of TBG may be useful in the assessment of pre-eclamptic pregnancies.…”
Section: Introductionmentioning
confidence: 99%